Implementation Of The Argonoleptic Test Of Purple Sweet Potatoes BasicBiscuits As A Processing Innovation Of Mp-Asi Ages 6 – 12 Months: Implementasi Uji Argonoleptik Biskuit Berbahan Dasar Ubi Jalar UnguSebagai Inovasi Pengolahan Mp-Asi Usia 6 – 12 Bulan - Nita Tri Putri; Vedjia Medhyna; Anjali Shakila (KPN Kopertis X, 2022)
This Community Service (PKM) aims to add insight and knowledge about the importance of writing scientific papers, techniques, and procedures for writing scientific publication articles, concepts, and techniques for publishing articles in national scientific journals, to the management of Scientific Publication Journals. Infancy is the most important period because it is a period that is very vulnerable to malnutrition. The provision of breast milk substitutes (MP-ASI) has an important role in overcoming the problem of malnutrition in infants. Purple sweet potatoes can help meet nutritional needs because they contain complex nutrients, namely carbohydrates, protein, fat, vitamins, iron, fiber, and anthocyanins. This type of research is an experiment that aims to determine the organoleptic test on biscuits substituted with purple sweet potato flour. The research population was mothers of infants aged 6-12 months and infants aged 6-12 months with a total population of 293 people. The sampling technique was purposive sampling with a total sample of 29 mothers of infants aged 6-12 months and 29 infants aged 6-12 months. The results of the organoleptic test showed that the level of preference for color was very like (38%) liked (55%) taste was very like (55%) liked (45%), the texture was very like (31%) liked (48%), the aroma was very like (34 %) liked (48%) and the acceptability test for 6-12 months babies liked it (93%). The results of this study can be useful as complementary foods for breast milk so that it can meet the daily nutritional needs of babies. It is recommended that further research be carried out to increase the preference value on the color, texture, and aroma of purple sweet potato biscuits